Metaphors in the Collection of Amygdala Song Lyrics: A Semantic Study - Fikriyah Layaly; Hesti; Neneng Nurjanah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
The use of metaphorical figures of speech in a song is an expression of the songwriter's emotions towards something that touches his heart and experiences it in the reality of life. The purpose of this research is to find out the types of metaphors used in the lyrics of the songs Kukira Kau Rumah, Tuhan Sebut Sia–Sia, and Balada Puan. This study used a descriptive qualitative approach with note-taking techniques. Data sourced from a collection of Amidala song lyrics. The results of the study show that in the three lyrics of the song Amygdala, there are source domains, target domains, types of metaphors, and the meanings of metaphorical expressions. The types of metaphors found are abstracting metaphors and the most commonly found metaphor is the word house.